2019
DOI: 10.5539/ass.v16n1p54
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Wellbeing Among Rural Migrant Workers in China: Did the 2008 Financial Crisis Worsen Their Vulnerability?

Abstract: Background. Since 1980, China has been experiencing the largest migration in human history to urban areas. Rural migrant workers are exposed to disproportionate stress, a sense of marginality, language barriers and low social positions. Stress plays a significant role in the development of psychosocial challenges, including anxiety, hostility and depressive symptoms, as well as diagnosable conditions, including compulsive and post-traumatic stress disorders. This project questions whether rural migrant workers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…Previous findings have shown that educational level and monthly income are determinants of financial behaviour and FWB ( Shusha, 2016 ), explained that people with better income and higher educational levels exhibit better financial behaviour and higher perceived FWB. From the literature, it was found that researchers have focused on financial aspects of vulnerable groups of society particularly the low-income households (e.g., Loibl, 2017 ; Hung, 2020 ; Magli et al, 2021 ). However, there appears to be very scant number of studies that address a specific segment of the vulnerable group, i.e., the young adults of low-income households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous findings have shown that educational level and monthly income are determinants of financial behaviour and FWB ( Shusha, 2016 ), explained that people with better income and higher educational levels exhibit better financial behaviour and higher perceived FWB. From the literature, it was found that researchers have focused on financial aspects of vulnerable groups of society particularly the low-income households (e.g., Loibl, 2017 ; Hung, 2020 ; Magli et al, 2021 ). However, there appears to be very scant number of studies that address a specific segment of the vulnerable group, i.e., the young adults of low-income households.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Existing studies on FWB and financial behaviour have predominantly focused their attention on the financial circumstances of vulnerable society, particularly low-income households [ 28 , 29 , 64 ]. However, it would appear that there are just a limited number of research that focus on a certain segment of the population that is vulnerable, specifically young adults who come from families with poor incomes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The relevant literature argues that rural-to-urban migrant workers and their dependents have been experiencing discrimination, exclusion, and stigmatization in the urban labor market and social space, thereby jeopardizing their mental health to a large extent (Hung, 2019;Yang et al, 2021). Supporting literature shows that rural-to-urban migrants suffered from more mental health issues (such as depression) than their native urban or rural counterparts, possibly because their disproportional encounters with deprivation and socioeconomic discrimination and disadvantages (Li and Rose, 2017).…”
Section: Introductionmentioning
confidence: 99%